Evaluation of the Effects of Residual Resin Removal and Polishing on the Enamel Surface, after Bracket Debonding - Carlos Eduardo de Oliveira Lima; Luíz Sérgio Carreiro; Paulo Eduardo Bággio; Pedro Marcelo Tondelli; Ricardo Takahashi; Ane Caroline Godoi da Silva (Portal de Periódicos da Marinha do Brasil, 2023)
Considering the use of specific burs to remove residual resin after bracket debonding and the possibility of injuries to the dental enamel after using these burs, this study aimed to verify the variation in the enamel surface appearance in a qualitative way and evaluation with topographic images of the dental enamel. The use of Scanning Electron Microscopy (SEM) allowed to illustrate and evaluate the enamel surface after the final polishing phase using two methods: rubber cup or Robinson brush. Twenty-five human premolar teeth were obtained from extractions in patients who voluntarily sought the Oral Maxillofacial Surgery Residency at the Dental School from the State University of Londrina; the teeth were divided into four groups A, B, C and D containing 6 teeth each according to the burs used to remove the remaining adhesive and the chosen polishing, in addition to one tooth as a "control". Dental enamel surface roughness was evaluated after resin removal and enamel surface after polishing with the two methods presented. The results showed that by observation and inspection, the burs removed residual resin from all teeth, however, caused scratches and grooves as evidenced in the SEM images. Based on the results, there was no statistical difference between the polishing methods, and both were important for the reduction of abrasive marks and provided a smoother enamel surface.